Caspase-1: A Promising Target for Preserving Blood–Brain Barrier Integrity in Acute Stroke - Ye, Xiaodong; Song, Guini; Huang, Shanshan; Liang, Qiming; Fang, Yongkang; Lian, Lifei; Zhu, Suiqiang (Frontiers in Molecular Neuroscience, 2022)
Blood-brain barrier (BBB) acts as a physical and biochemical barrier which plays a fundamental role in regulating the blood-to-brain influx of endogenous and exogenous components and maintaining the homeostatic microenvironment of the central nervous system. Acute stroke leads to BBB disruption, blood substances extravasation into brain parenchyma and the consequence of brain edema formation with neurological impairment afterwards. Caspase-1, one of the evolutionary conserved families of cysteine proteases, which is upregulated in acute stroke, mainly mediates pyroptosis and compromises BBB integrity via lytic cellular death and inflammatory cytokines release. Nowadays, targeting caspase-1 has been proven effective in decreasing the occurrence of hemorrhagic transformation and in attenuating brain edema and secondary damages during the acute stroke. However, the underlying interactions among caspase-1, BBB and stroke still remain ill-defined yet. Hence, in this review, we will concern about the roles of caspase-1 activation and its associated mechanisms in stroke-induced BBB damage, aiming at providing insights into the significance of caspase-1 inhibition on stroke treatment in the near future.